Plant-derived smoke water and karrikinolide (KAR1) enhance physiological activities, essential oil yield and bioactive constituents of Mentha arvensis L. - Singh, Sarika; Uddin, Moin; Chishti, Aman Sobia; Bhat, Urooj Hassan; Singh, Sangram; Khan, M. Masroor A. (Frontiers in Plant Science, 2023)
Plant-derived smoke water (PDSW) is made from the burning of dried wheat straw and acts as a growth-promoting substance that is economical and bioactive at very low concentrations. Karrikinolide (KAR1) is one of the bioactive constituents of plant-derived smoke water. The experimental work presented in the current study was carried out with the hypothesis that foliar application of PDSW and karrikinolide enhanced the plant growth, physiology, and essential oil production of the mint plant. Different concentrations of PDSW (1:125, 1:250, 1:500 and 1:1000 v/v) and KAR1 (10-9 M, 10-8 M, 10-7 M and 10-6 M) were used in foliar application on Mentha arvensis L. along with control (double-distilled water). Results indicated that 1:500 v/v of PDSW and 10-8 M of KAR1 proved optimal in enhancing all morphological, physiological, and essential oil yield-related parameters. In comparison with the control, 1:500 v/v of PDSW and 10-8 M of KAR1 increase the height of mint plant (19.23% and 16.47%), fresh weight (19.30% and 17.44%), dry weight (35.36% and 24.75%), leaf area (18.22% and 17.46%), and leaf yield per plant (28.41% and 23.74%). In addition, 1:500 v/v of PDSW and 10-8 M of KAR1 increase the photosynthetic parameters, including chlorophyll fluorescence (12.10% and 11.41%), total chlorophyll content (25.70% and 20.77%), and carotenoid content (29.77% and 27.18%), in comparison with control. Likewise, 1:500 v/v of PDSW and 10-8 M of KAR1 increase the essential oil content (37.09% and 32.25%), essential oil productivity per plant (72.22% and 66.66%), menthol content (29.94% and 25.42%), menthyl acetate content (36.90% and 31.73%), and menthone content (44.38% and 37.75%) in comparison with the control. Furthermore, the TIC chromatogram of the GCMS analysis reveals the presence of 34 compounds, 12 of which are major peak areas. Therefore, 1: 500 v/v of plant-derived smoke water shows significant results as compared to those of KAR1 and control treatments and might be used as a recommendation tool for agricultural and horticultural crops, as the difference between the costs of two chemicals is huge.